Exploring the Functional Relationship between y-Type Thioredoxins and 2-Cys Peroxiredoxins in Arabidopsis Chloroplasts - Ana Jurado-Flores; Víctor Delgado-Requerey; Alicia Gálvez-Ramírez; Leonor Puerto-Galán; Juan Manuel Pérez-Ruiz; Francisco Javier Cejudo (MDPI AG, 2020)
Thioredoxins (Trxs) are small, ubiquitous enzymes that catalyze disulphide-dithiol interchange in target enzymes. The large set of chloroplast Trxs, including f, m, x and y subtypes, use reducing equivalents fueled by photoreduced ferredoxin (Fdx) for fine-tuning photosynthetic performance and metabolism through the control of the activity of redox-sensitive proteins. Although biochemical analyses suggested functional diversity of chloroplast Trxs, genetic studies have established that deficiency in a particular Trx subtype has subtle phenotypic effects, leading to the proposal that the Trx isoforms are functionally redundant. In addition, chloroplasts contain an NADPH-dependent Trx reductase with a joint Trx domain, termed NTRC. Interestingly, Arabidopsis mutants combining the deficiencies of x- or f-type Trxs and NTRC display very severe growth inhibition phenotypes, which are partially rescued by decreased levels of 2-Cys peroxiredoxins (Prxs). These findings indicate that the reducing capacity of Trxs f and x is modulated by the redox balance of 2-Cys Prxs, which is controlled by NTRC. In this study, we explored whether NTRC acts as a master regulator of the pool of chloroplast Trxs by analyzing its functional relationship with Trxs y. While Trx y interacts with 2-Cys Prxs in vitro and in planta, the analysis of Arabidopsis mutants devoid of NTRC and Trxs y suggests that Trxs y have only a minor effect, if any, on the redox state of 2-Cys Prxs.